Establishing equivalence–equivalence analogical relations via tact and listener training. Issue 1 (14th December 2020) - Cordeiro, Maria Clara; Zhirnova, Tatiana; Miguel, Caio F.
Abstract : We investigated the role of verbal behavior on the emergence of analogy‐type responding as measured via equivalence–equivalence relations. In Experiment 1, 8 college students learned to label arbitrary stimuli as, "vek, " "zog, " and "paf", and in Experiment 2, 8 additional participants learned to select these stimuli when hearing their names in an auditory–visual matching‐to‐sample (MTS) task. Experimenters tested for the emergence of relational tacts (i.e., "same" and "different") and equivalence–equivalence relations (analogy tests) via visual–visual MTS. Half of the participants were exposed to a think‐aloud procedure. Even though they all passed analogy tests while tacting stimuli relationally, only participants exposed to tact training (Experiment 1) did so without the need for remediation. The results of these experiments confirm that individual discriminative and relational control of stimuli established through verbal behavior training is sufficient to produce equivalence–equivalence analogical responding, advancing the analysis of complex cognitive (problem‐solving) phenomena.